Occupational noise level in mechanized and semimecanized harvest of coffee fruits - da Silva, José Antonio Ramos; de Oliveira Júnior, Geraldo Gomes; de Melo Costa, Carlos Emanuel; da Silva, Adriano Bortolotti; Gabriel, Camila Pires Cremasco [UNESP]; Putti, Fernando Ferrari [UNESP] (Coffee Science, 2018)
Coffee cultivation has undergone significant changes, especially with regard to the mechanization process of the various existing operations that were previously carried out manually by the workers. It is observed that the intensification of mechanized activities can expose workers to noise levels capable of compromising their hearing health. In this sense, the objective in the present study was to determine the level of occupational noise in the activities of mechanized and semimechanized harvesting of coffee fruits and compare them with the limits of tolerance of the current legislation. The occupational noise level was determined considering the exposure of homogeneous groups, using an integrative meter for personal use, noise dosimeter, electromechanically calibrated and with field calibration. The results demonstrate that the noise levels found are above the limits allowed for an 8-hour working day. The highest observed level was 100.7 dB (A) in the sweeping operation with the blower equipment and the lowest level 89.0 dB (A) in the auxiliary activity of the selected collection equipment Vicon H3000. Harvesting activity with a portable mechanical stripper equipment showed a noise level 4.2% higher compared to harvesting with automotive harvester equipment.
Nível de ruído ocupacional na colheita mecanizada e semimecanizada dos frutos do cafeeiro
Keywords: Coffee cultivation; Mechanization; Occupational risk